Analisis Pengaruh Kedalaman Insulasi Riser Terhadap Kinerja Termal dan Tekno - Ekonomi Sistem Geothermal Closed-Loop Berbasis Co2 - Muhammad Robith Atho'illah; Nugroho Agung Pambudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
AbstractThe closed-loop geothermal system (CLGS) utilizing supercritical carbon dioxide (sCO2) is a promising technology, yet its thermal efficiency is significantly affected by heat loss as the fluid flows upward to the surface through the production pipe (riser). The application of Vacuum Insulated Tubing (VIT) on the riser is proven effective in suppressing thermal losses, but it presents a financial trade-off due to high capital expenditure (CAPEX). This study aims to analyze the effect of riser insulation depth variations on the thermal performance of sCO2 wells and the power generation performance of an Organic Rankine Cycle (ORC) utilizing R245fa working fluid, as well as to evaluate its techno-economic aspects to determine the optimal insulation depth that yields the lowest Levelized Cost of Electricity (LCOE). The method used in this research is numerical modeling and simulation of a U-shaped geothermal system configuration. Variations were applied to the insulation depth ranging from 0 meters (uninsulated) to the maximum well depth, evaluating changes in parameters such as outlet temperature, heat extraction rate, natural thermosiphon effect, ORC net power output, and economic feasibility indicators. The results show that increasing insulation depth has a significant impact on the system's thermal performance. Increasing the insulation depth from 0 m to the optimum point of 2,750 m increased the fluid production temperature from 111.27 °C to 127.13 °C and raised the heat extraction rate from 1.949 MW to 2.472 MW. This improvement in thermal quality directly impacted the increase in ORC net electric power by 26.83%, from 0.2339 MW to 0.2966 MW. From a techno-economic perspective, the insulation depth of 2,750 m was determined as the financial sweet spot, generating a minimum LCOE of 0.96991 USD/kWh, which is a 13.51% decrease compared to the uninsulated system. In conclusion, determining the precise insulation depth is highly crucial in maximizing thermodynamic performance while maintaining the financial feasibility limits of the CLGS power plant infrastructure